7q31.2q31.31 deletion downstream of FOXP2 segregating in a family with speech and language disorder. Issue 11 (4th September 2020) - Rieger, Melissa; Krumbiegel, Mandy; Reuter, Miriam S.; Schützenberger, Anne; Reis, André; Zweier, Christiane
Abstract: Chromosomal 7q31 deletions have been described in individuals with variable neurodevelopmental phenotypes including speech and language impairment. These copy number variants usually encompass FOXP2, haploinsufficiency of which represents a widely acknowledged cause for specific speech and language disorders. By chromosomal microarray analysis we identified a 4.7 Mb microdeletion at 7q31.2q31.31 downstream of FOXP2 in three family members presenting with variable speech, language and neurodevelopmental phenotypes. The index individual showed delayed speech development with impaired speech production, reduced language comprehension, and additionally learning difficulties, microcephaly, and attention deficit. His younger sister had delayed speech development with impaired speech production and partially reduced language comprehension. Their mother had attended a school for children with speech and language deficiencies and presented with impaired articulation. The deletion had occurred de novo in the mother, includes 15 protein‐coding genes and is located in close proximity to the 3′ end of FOXP2 . Though a novel locus at 7q31.2q31.31 associated with mild neurodevelopmental and more prominent speech and language impairment is possible, the close phenotypic overlap with FOXP2 ‐associated speech and language disorder rather suggests a positional effect on FOXP2 expression and function.